Kesenjangan Implementasi Kebijakan Pendidikan Dasar di Indonesia: Analisis antara Desain Kebijakan dan Praktik Layanan Pendidikan - Hapsari, Melati Indri; Handoyo, Eko; Rokhman, Fathur (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Basic education is a strategic foundation for human resource development and a fundamental right of every Indonesian citizen as mandated by the 1945 Constitution. The development of basic education policies in Indonesia is directed toward improving access, equity, learning quality, and educational relevance to social dynamics and contemporary challenges. This article aims to describe basic education development policies in Indonesia, analyze their implementation, and identify challenges and development strategies. This study employs a qualitative approach using the library research method. Data was collected through documentation studies of regulations, scientific literature, and relevant research findings, then analyzed descriptively. The findings indicate that policy implementation has been carried out through various strategic programs, including the compulsory nine-year education policy extended toward thirteen years, implementation of National Education Standards, development of the Independent Curriculum, equalization of educational access, strengthening educational governance, and improving teacher competencies. These policies have positively contributed to increasing participation in basic education. However, implementation still faces challenges such as disparities in educational quality across regions, limited infrastructure, low digital literacy, and uneven teacher distribution. Therefore, evidence-based policy strengthening, equitable educational facilities, continuous teacher competency development, and multi-stakeholder collaboration are essential to achieve quality and inclusive basic education in Indonesia.